The classification of religion in religious studies and modern neo-paganism - Асанова, С. С.; Абжалов, С. У. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The article examines the typological relationship of contemporary neo-paganism and early forms of religious belief. The author based on this classification, religious studies religion, tries to trace the genetic origins, the process of formation and evolution of the complex neo-pagan religious ideas and beliefs. This explains the appeal of the author’s classification of religion Hegel, M. Mueller, K. Thiele. Based on these classifications, the author seek to determine the classification of modern neo-paganism. Key words: religion, classification of religion, language, the language of the family, a religious family, polytheism, politism, natural religion, ethical religion, particularistic religion, universal religion.